Support models for sustainable development of small cities - V. I. Aleshnikova (Вестник университета)
The article is devoted to the study of the tools and mechanisms’ effectiveness for supporting small cities in Russian Federation. The topic relevance is due to the negative trends in the development of such cities and the need to improve the approach to the formation of measures to ensure the stability of their functioning. The aim is to substantiate the use of different models to support the sustainable development of small cities. Methods of monographic, comparative, economic and statistical analysis are used in the work. According to the study results of tools for supporting small cities in Russia and in the Central Chernozem Region, a conclusion was made about their low efficiency, weak use of regional, municipal and public measures. The necessity of systematic and integrated approaches to solving the problem of increasing sustainability is argued. Within the framework of these approaches, it is proposed to systematize tools and mechanisms to support the development of small cities, taking into account their key competencies by levels (federal, regional, municipal, public) and types of problems. As a result, the visualized tools in the form of a matrix are the basis for the formation of various models for supporting the sustainable development of small cities, taking into account the interests of target audiences. The practical significance of the study lies in the possibility of using proposals for designing programs and projects for small cities’ development.